2014
DOI: 10.1111/petr.12349
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of duct‐to‐duct vs. Roux‐en‐Y hepaticojejunostomy biliary anastomoses in below 15‐kg pediatric liver transplant recipients

Abstract: The best type of biliary anastomosis to use in lower weight pediatric liver transplant recipients is debatable. In this study, we share a single center's experience comparing the rate of anastomotic biliary complications based on the type of biliary anastomosis performed in this population of patients. A retrospective review of pediatric liver transplants for recipients weighing <15 kg from 11/2003 till 12/2011 was performed. Patients were grouped based on the type of biliary anastomosis into two groups: duct-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
5
0
2
Order By: Relevance
“…A previous study showed that there was no statistically significant difference in postoperative anastomotic biliary complications between duct-to-duct and Roux-en-Y hepaticojejunostomy biliary re construction in pediatric liver transplant recipients weighing < 15 kg. 14 The HAT is a severe complication following liver transplant with a high risk for short-or long-term graft dysfunction and biliary complications. Early after surgery, HAT has a mortality rate of 50%.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that there was no statistically significant difference in postoperative anastomotic biliary complications between duct-to-duct and Roux-en-Y hepaticojejunostomy biliary re construction in pediatric liver transplant recipients weighing < 15 kg. 14 The HAT is a severe complication following liver transplant with a high risk for short-or long-term graft dysfunction and biliary complications. Early after surgery, HAT has a mortality rate of 50%.…”
Section: Discussionmentioning
confidence: 99%
“…Эволюция методов трансплантации печени привела к улучшению результатов лечения пациентов. В литературе недостаточно данных о результатах использования двух рассматриваемых методов реконструкции желчевыводящих путей при трансплантации печени [10]. Целью этого исследования было сравнить результаты билиарной реконструкции «проток в проток» и гепатикоеюностомии на петле по Ру у детей -реципиентов печени с массой тела менее 15 кг.…”
Section: Abstract: Liver Transplantation Duct-to-duct Biliary Reconstructions Roux-en-y Hepaticojejunostomy Biliary Complicationsunclassified
“…Впоследствии из исследования исключили 46 человек из группы 1 и 43 человека из группы 2. Средний возраст пациентов составил 2,468 ± 1,5711 года (0,5-10), а их средний вес составил 10,403 ± 2,5501 кг (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Наиболее частыми заболеваниями, потребовавшими проведения операции, были атрезия желчевыводящих путей (32%), PFIC -прогрессирующий внутрипеченочный холестаз (17,1%), тирозинемия (16%) и синдром Криглера-Найяра (10,5%).…”
Section: результаты исследования дооперационные характеристики пациентовunclassified
See 2 more Smart Citations